There’s More to IT Outsourcing than Meets the Eye - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
As IT outsourcing continues to grow, this highly complex business poses interesting challenges that are not always fully understood, especially when large -scale projects are being implemented. At the 4th Annual Business Leadership Seminar of the Singapore Computer Society (SCS), held at the Singapore Management University in April 2008, CIOs from several leading public and private organisations discussed the pros and cons of IT outsourcing.